2014
DOI: 10.5339/gcsp.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Tissue plasminogen activator-based clot busting: Controlled delivery approaches

Abstract: Cardiovascular diseases are the leading cause of death worldwide. Thrombosis, the formation of blood clot (thrombus) in the circulatory system obstructing the blood flow, is one of the main causes behind various ischemic arterial syndromes such as ischemic stroke and myocardial infarction, as well as vein syndromes such as deep vein thrombosis, and consequently, pulmonary emboli. Several thrombolytic agents have been developed for treating thrombosis, the most common being tissue plasminogen activator (tPA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…Standard dosage used in CLOTBUST was: standard intravenous tPA (0.9 mg/kg body weight, 10 % as bolus, the remainder over 1 hour) in combination with 2-hours continuous 2-MHz diagnostic transcranial Doppler (TCD) ultrasound. Moreover, it has been found that lower ultrasound frequencies (e.g., 300 kHz, in kilohertz) can cause higher rates of intracerebral hemorrhage 59 , whereas the diagnostic frequencies (e.g.,2-MHz, in megahertz) show no such side effect and are safe enough to be used in humans 57, 58, 60 .…”
Section: Nanocarriers For Tpamentioning
confidence: 99%
“…Standard dosage used in CLOTBUST was: standard intravenous tPA (0.9 mg/kg body weight, 10 % as bolus, the remainder over 1 hour) in combination with 2-hours continuous 2-MHz diagnostic transcranial Doppler (TCD) ultrasound. Moreover, it has been found that lower ultrasound frequencies (e.g., 300 kHz, in kilohertz) can cause higher rates of intracerebral hemorrhage 59 , whereas the diagnostic frequencies (e.g.,2-MHz, in megahertz) show no such side effect and are safe enough to be used in humans 57, 58, 60 .…”
Section: Nanocarriers For Tpamentioning
confidence: 99%
“…[9][10][11] TPA is a serine protease which catalyzes the conversion of plasminogen to plasmin, the primary enzyme which degrades fibrin, causing the fibrinolysis which results in clot dissolution. 12,13 TPA may be used intravenously or locally (i.e., through a catheter) in the treatment of conditions resulting from thrombus formation, such as myocardial infarction, pulmonary embolism, and peripheral arterial disease. 14,15 Current clinical use of IV tPA is limited by its narrow therapeutic time window, hemorrhagic complications, and suboptimal delivery to the precise location of the thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Current clinical use of IV tPA is limited by its narrow therapeutic time window, hemorrhagic complications, and suboptimal delivery to the precise location of the thrombus. 7,8,13,16,17 In computational studies, IV administration of a thrombolytic such as tPA to a thrombus situated within an occluded blood vessel occurs primarily as a function of the length of the occluded vessel and may take 2-3 hrs for peak delivery. 18 It has been estimated that less than 1/100,000% of drug administered intravenously actually reaches the offending blood clot.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations have prompted researchers to improve thrombolysis by developing artificial PAs that are more enzymatically active, using adjuvants that assist PA, or inhibiting PAI‐1 or factor XIIIa . Another approach is to modify PAs with macromolecules to protect them from clearance and degradation in blood, thereby improving circulation half‐life . Further modifications of PA facilitate thrombus targeting via functionalization with moieties that bind to activated platelets or fibrin .…”
Section: Introductionmentioning
confidence: 99%
“…26 Another approach is to modify PAs with macromolecules to protect them from clearance and degradation in blood, thereby improving circulation half-life. 27,28 Further modifications of PA facilitate thrombus targeting via functionalization with moieties that bind to activated platelets or fibrin. 29 However, these approaches offer only marginal improvements over tPA, rely on blood flow for delivery, and still exhibit high risk of bleeding.…”
Section: Introductionmentioning
confidence: 99%